Deposition of whole blood platelets on extracellular matrix under flow conditions in preterm infants. Issue 2 (1st March 2002) - Linder, N; Shenkman, B; Levin, E; Sirota, L; Vishne, T H; Tamarin, I; Dardik, R; Lubin, D; Savion, N; Varon, D
Abstract : Background: A previous study showed greater adhesion by platelets of healthy full term infants to subendothelial extracellular matrix (ECM) under flow conditions compared with healthy adult platelets. Aim: To investigate the adhesion and aggregation of platelets from preterm infants on ECM under defined shear conditions. Methods: In vitro platelet function was investigated in 106 preterm infants, 74 full term infants, and 26 healthy adults. Blood samples were obtained from all infants within 24 hours of birth, and weekly until discharge from preterm infants only. Citrated whole blood was placed in ECM precoated tissue culture plates and subjected to shear stress (1300 s −1 ) for two minutes using a rotating Teflon cone. Platelet adhesion (surface coverage) and aggregation (average size) to ECM were assayed using an image analyser. Assays for von Willebrand factor (vWF) antigen, ristocetin cofactor, and vWF collagen-binding activity were performed on samples from an additional 70 preterm infants, 23 healthy full term infants, and 24 healthy adults. Preterm infants with hyaline membrane disease (HMD) were analysed separately in both cohorts. Results: Platelets from preterm infants displayed significantly less platelet adhesion than those from full term infants but similar aggregation and levels of vWF antigen, ristocetin cofactor, and collagen binding activity. Mean surface coverage was 22.0 (8.4)% for preterm infants with HMD, 28.7 (8.0)% for healthy preterm infants, and 35.7 (7.9)% for full term infants. Surface coverage in the preterm infants correlated with gestational age during the first 24 hours only, and did not reach full term levels during 10 weeks of follow up. Conclusion: Platelet adhesion to ECM is significantly poorer in preterm than in full term infants, and poorer in preterm infants with HMD than in healthy preterm infants. Intrinsic platelet properties rather than the concentration or activity of vWF may be responsible for this difference.